Habitat as a Service. From Bespoke to Custom Interiors - Raffaella Fagnoni; Davide Crippa; Annapaola Vacanti (Pad, 2023)
The article discusses the transformation of the Italian domestic environments in the wake of the Covid-19 pandemic and the impact of digital technology. It highlights two key trends: the hybridization of domestic spaces due to remote work, study, training, and socialising facilitated by digital tools, and the increasingly dynamic lifestyles of young people, particularly millennials and Generation Z, who tend to live in rented spaces and embrace remote work. It is then arguable that the identitarian value of domestic spaces is changing, as physical objects and furniture become more interchangeable due to the fast-paced and unpredictable lives of young individuals. This shift must prompt a discussion about how interior design is adapting to such sociological changes. Various options are available for designers to create value through sharing and renting services, drawing inspiration from similar models in the office furniture sector. The primary aim of the paper is to present novel scenarios for the design of domestic spaces, as the servitization of business models offers opportunities to reconsider how products and furniture are acquired and used, particularly as more adults don’t own the homes they live in and frequently change residences. Renting is proposed as an effective model for creating more agile and customizable spaces that align with contemporary lifestyle preferences.